Enhancing Madrasas' Competitive Edge: The Power of Effective Governance Systems - Cholid, Nur; Saepurohman, Aep; Ulumuddin, Imam Khoirul; Wibowo, Adi (JURNAL AL-TANZIM, 2024)
This research aims to explore the factors that contribute to increasing the competitive advantage of educational institutions through implementing an effective governance system. A qualitative approach with a case study design was used in this research. The location of the research was MI Gedanganak and SD Hj. Isriati Moenadi, East Ungaran District, Semarang Regency. Data collection methods include observation, in-depth interviews, and document analysis. Data analysis was carried out thematically to identify governance patterns in the two educational institutions. The research results show that the two institutions, MI Gedanganak and SD Hj. Isriati Moenadi is included in the category that excels in its management. MI Gedanganak is recognized as having excellence in madrasa management, including curriculum, student, teaching staff, finance, and infrastructure management. Meanwhile, SD Hj Isriati Moenadi Ungaran is also known for its excellence in school management, including curriculum management, students, teaching staff, finances, and infrastructure. Both institutions use a holistic Islamic learning approach, emphasizing integrating Islamic concepts, knowledge, and skills. The implication of this research is to provide a deeper understanding of the governance practices of educational institutions and their contribution to increasing the competitive advantage of Islamic educational institutions.